El aprendizaje basado en problemas en la formación de profesionales de la salud, Rionegro-Antioquia: 1996 (1997)
ABSTRACT: In this article, a research carried out in the UNI-Rionegro Program is presented. The program involved teachers and students from the Nursing, Medicine, Dentristy, Bacteriology, and Nutrition Schools at the University of Antioquia in Medellín-Colombia. The following objetives were drawn: 1) to get together conceptual and methodological elements oriented towards the construction of a curriculum on the bases of solving problems from an experience of Problems Base don Learning (PBL); 2) to observe results in the field of declarative knowledge and abilities to solve problems; 3) to observe results in interdisciplinary education; and 4) to detect the strengths and weaknesses of the PBL methodology in this kind of education with community participation. As an independent variable, we worked with a triple treatment as follows: PBL methodology, interdisciplinary work, and community participation. On the other hand, The observation of effects of the treatment on participants´ specific knowledge, the development of the community in the solution of their problems, as well as students´and theachers´ attitudes facing the method were selected as independent variables. As an experimental simple, the population to be evaluated by means of dependent variables were students and teachers from the professions above mentioned acting as take-carers in children´s homes, At the same time, a control simple of students from the same careers and levels that attended to other fields of practice under ability test was built in order to get information from the dependent variables. Starting from a central problem, students generated by-problems from the following four nuclei: diagnosis of children´s homes, health promotion, children´s growing and development, and interdisciplinary work and team work. These topics were approached by means of documentation, direct observation, relationships, explanation, and generation of new by-problems. The methodological design was performed involving a mixed framework both qualitative and quantitative. A quasi-experimental design was applied for the variable abilities and the final analysis was followed among averages of pretest and posttest gains in the experimental and control groups. For the other variables, a qualitative design of building of conceptual categories and an analysis of it was carried out, having as a guide the purposes of the investigation. Teachers´ and students´daily observation sheets werw the main source of these analyses as well an meetings in which the students´ and teachers´ interdisciplinary work was promoted. Finally, the results achieved by teachers-investigators as a whole, searching for intersubjetive observation, and methodological triangulation, say, questionnaires, observations, and the reading of daily observation sheets were encouraging in these variables: attitudes, abilities, interdisciplinary work, methodological change, close-up to the community problems. Inferences were statistically and qualitatively significant.